Transformasi Tes Diagnostik dalam Pendidikan: Konsep, Pengembangan, dan Implementasinya untuk Mewujudkan Pembelajaran Adaptif - Nuruddin; Ahmad Rasyid Ridho (TSAQOFAH, 2026)
Diagnostic tests are a form of assessment that serves to identify students’ initial abilities, misconceptions, learning difficulties, and needs before and during the learning process. The shift in the twenty-first-century educational paradigm toward differentiated and adaptive learning has further strengthened the strategic role of diagnostic tests in supporting effective, meaningful, and student-centered learning. This article aims to examine the concepts, characteristics, development principles, preparation stages, implementation, and challenges and opportunities associated with applying diagnostic tests in adaptive learning in the digital era. The study employed a library research method with a qualitative descriptive approach through an analysis of books, national and international journal articles, and relevant educational policy documents. The findings indicate that diagnostic tests function not only as tools for measuring initial abilities but have also developed into instruments for data-driven instructional decision-making. The integration of digital technology enables diagnostic tests to be administered automatically, adaptively, rapidly, and accurately, allowing teachers to design learning strategies suited to students’ characteristics and needs. The implementation of diagnostic tests also supports the application of the Kurikulum Merdeka through differentiated learning, formative assessment, and improvements in the quality of student-centered educational services. This study concludes that the effectiveness of diagnostic tests in adaptive learning largely depends on teachers’ competence in designing instruments, interpreting assessment results, and using them as a basis for developing learning strategies. These findings strengthen the literature on educational assessment and emphasize the importance of developing teachers’ competencies and utilizing digital technology to achieve high-quality adaptive learning.